2012
DOI: 10.1016/j.jcmg.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Accuracy and Reproducibility of RV Volume Measurements by CMR in Congenital Heart Disease

Abstract: Trends favoring the axial orientation in terms of reproducibility were not clinically significant. In subjects with RV EDV ≥ 150 ml/m(2), the axial orientation yields RV volume measurements that agree more closely with flow measured in the pulmonary trunk than does the short-axis orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 31 publications
0
54
0
Order By: Relevance
“…For each subject, breath-held segmented 2D bSSFP cine images were acquired in the 4-chamber orientation with a stack of images in the short axis orientation covering the entire RV. The use of short axis images was based on both clinical experience and recent data showing statistical equivalence in the measurement of RV parameters using short axis or axial planes [24]. For each 2D image, data was acquired using three different imaging techniques (detailed imaging parameters are delineated in Table 1):…”
Section: Cmr Protocolmentioning
confidence: 99%
“…For each subject, breath-held segmented 2D bSSFP cine images were acquired in the 4-chamber orientation with a stack of images in the short axis orientation covering the entire RV. The use of short axis images was based on both clinical experience and recent data showing statistical equivalence in the measurement of RV parameters using short axis or axial planes [24]. For each 2D image, data was acquired using three different imaging techniques (detailed imaging parameters are delineated in Table 1):…”
Section: Cmr Protocolmentioning
confidence: 99%
“…To cover both ventricles from base to apex, a stack of images is required usually in the short-axis plane. Some authors, however, reported more accurate RV volume measurements in CHD when using images acquired in an axial orientation 16. In adult patients with PH, a large RV volume, a reduced RV ejection fraction and a reduced LV volume as evaluated by CMR have been repeatedly identified as independent predictors of mortality and treatment failure 17 18.…”
Section: Cardiac Magnetic Resonancementioning
confidence: 99%
“…Studies by Hudsmith et al 16 and Grothues et al 15 reported similar interobserver coefficients of variations for RV measurements. Clarke et al 17 compared the observer variability of RV volume measurements between images obtained in the short-axis plane versus the axial plane in 50 patients with CHD. The intra- and interobserver reliability of RV end-diastolic volume, end-systolic volume, and stroke volume measurements was excellent for both contouring methods.…”
Section: Cmr Is the Gold Standard For Noninvasive Measurements Of Rv mentioning
confidence: 99%